Factors Affecting The Effectiveness of Application Local Regulation of Cigarette Free Areas in Puskesmas Balangan District - Herry Rusandy; Ruslan Muhyi; Erida Widyamala; Husaini Husaini; Lenie Marlinae (Lambung Mangkurat, 2021)
Indonesia is the third country of smokers in the world. It increases disease and death by 50% in developing countries. WHO launched